1999
DOI: 10.1556/aalim.28.1999.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of physico-chemical properties of bovine b-casein by nonenzymatic glycation associated with enzymatic dephosphorylation

Abstract: A major bovine casein fraction, β-casein was chemically glycated and/or enzymatically dephosphorylated. Ten glucose and nine lactose moieties were attached while all phosphate groups were removed. Glycation shifted the pI to acidic pH range and decreased the solubility at acidic pHs while dephosphorylation shifted the pI to neutral pH range and increased the solubility at acidic pHs. Dephosphorylation led to longer retention time measured using the reversed-phase high-performance liquid chromatography and affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…In our ealier study we found, that the covalent attachment of glucosyl residues to bCN improved its solubility in the pH range of isoelectric point, which was slightly shifted to the acidic pH [16]. Changes in the solubility can be caused by slight increase in the hydrophilicity of bCN after glycosylation.…”
Section: Emulsion Forming and Stabilizing Properties Of Intact And Glmentioning
confidence: 82%
“…In our ealier study we found, that the covalent attachment of glucosyl residues to bCN improved its solubility in the pH range of isoelectric point, which was slightly shifted to the acidic pH [16]. Changes in the solubility can be caused by slight increase in the hydrophilicity of bCN after glycosylation.…”
Section: Emulsion Forming and Stabilizing Properties Of Intact And Glmentioning
confidence: 82%
“…They explained this change by an increase in the flexibility of glycated casein allowing a more rapid absorption at the water-air interface (in comparison to nonglycated caseins). Darewicz et al (1999a) studied the impact of glycation and enzymatic dephosphorylation on β-casein. In this study, ten glucose and nine lactose were bound to casein while all phosphate groups were removed.…”
Section: Reaction With Sugarsmentioning
confidence: 99%
“…Consequently, this charge modification shifted the pHi value of caseins toward neutral pH and increased their solubility at acidic pH (Darewicz et al 1999a). Recently, McCarthy et al (2013) showed that dephosphorylation of β-casein increased its pH of minimum solubility from pH 5 to 5.5.…”
Section: Dephosphorylationmentioning
confidence: 99%
“…A number of studies have evaluated the effect of enzymatic dephosphorylation on the functional properties of caseins. In addition, dephosphorylated whole casein (Van Hekken and Strange, 1993) or b-casein (Darewicz et al, 1999;Darewicz and Dziuba, 2001) was found to be considerably less sensitive to calcium-induced insolubilization. Under suitable conditions, virtually complete dephosphorylation of caseins is achieved Strange, 1993, 1994).…”
Section: Enzymatic Dephosphorylation Of Milk Proteinsmentioning
confidence: 97%